Friendly Teaching Approaches and Teacher–Student Interactions in Islamic Education at Darul Qur’an Mafaza - Zaidan, Muchlis; Susilo, Mohamad Joko (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
Education in the pesantren environment is not solely oriented toward the transmission of Islamic knowledge, but also places strong emphasis on the cultivation of adab, character formation, and the development of educational relationships between ustadz and santri. Although attention to warm and dialogical interactions has increased, empirical research on friendly teaching in pesantren is still limited. This study therefore examines its implementation in Islamic Religious Education at Pesantren Darul Qur’an Mafaza, focusing on practices, teachers’ strategies, and students’ perceptions . The focus of the analysis includes the various practices applied in the learning process, the pedagogical strategies employed by teachers, and students’ perceptions of the educational relationships that develop both inside and outside the classroom. The research adopts a qualitative approach with a case study design. Data were collected through classroom observations, in-depth interviews with PAI teachers, students, and pesantren leaders, as well as an analysis of relevant documentation. The collected data were then analyzed thematically through stages of data reduction, data presentation, and conclusion drawing. The findings indicate that the friendly teaching approach at Pesantren Darul Qur’an Mafaza is manifested through the use of polite and respectful language, dialogical communication, the provision of open spaces for questioning, and personal mentoring that remains grounded in adab and the pedagogical authority of the ustadz. Teaching strategies emphasize a balance between firmness and emotional warmth, both in formal learning activities and in informal interactions. Students perceive this approach as creating a comfortable, non-threatening learning atmosphere that encourages them to participate actively. At the institutional level, these practices are reinforced by the pesantren culture, which positions role modeling and harmonious relationships as fundamental pillars of education. The novelty of this study lies in conceptualizing the friendly teaching approach within the pesantren context as a pedagogical practice rooted in the values of ta’dib, rahmah, and ta‘līm bi al-rifq, rather than merely as an adaptation of Western humanistic pedagogy. These findings affirm that relational warmth and the reinforcement of adab are not contradictory elements; instead, they mutually reinforce one another in fostering Islamic Religious Education that is humanistic, meaningful, and contextually grounded.